Investigation of Path Planning to Reduce Height Errors of Intersection Parts in Wire-Arc Additive Manufacturing - Gyeong-Hwan Song (MDPI AG, 2021)
Additive manufacturing (AM) has the advantages of reducing material usage and geometrical complexity compared to subtractive manufacturing. Wire arc additive manufacturing (WAAM) is an additive manufacturing process that can be used to rapidly manufacture medium-and large-sized products. This study deals with the path-planning strategy in WAAM, which can affect the quality of deposited components. It aims at suggesting effective path planning to reduce the height error of intersection parts. A comparative analysis of the bead width and height at the intersection parts was performed to verify the effectiveness of the proposed path. The initial parameters were determined through single-layer deposition experiments, and multi-layer deposition experiments were performed. The resultant height error in the intersection part was 0.8%, while that in the non-intersection part was absent at the maximum height. Path planning is considered to be an effective method.